A feasibility study of prompt capture gamma in vivo neutron activation analysis - Zamenhof, R G; Deutsch, O L; Murray, B W (Medical physics (Lancaster), 1979)
The feasibility of using the information contained in the radiative capture gamma ray spectrum of the neutron-irradiated human body to measure quantitatively total body elemental composition in vivo has been investigated. Results of time dependent Monte Carlo simulations have shown that spectral interference of nonradiative capture origin can be completely eliminated by pulsing the detector/spectrometer system in anticoincidence with the neutron source. Calculations based on the results of the Monte Carlo simulation and on an experimental measurement of the efficiency versus energy characteristics of a Ge(Li) detector suggest that the primary limitation of the proposed technique would be inter-element spectral interference rather than inadequate detector sensitivity. Experimental measurements using a pulsed 14-MeV neutron generator and Ge(Li) gamma-ray spectrometer have produced results that are consistent with the predictions of the theoretical model. A radiative capture gamma-ray spectrum of a tissue-equivalent phantom was measured in pulsed mode and analyzed offline using a computerized spectral analysis procedure. The results were scaled to a proposed facility consisting of a 2.5-MeV pulsed neutron source and a detection system comprising two 50-cm3 (Ge(Li) detectros past which the subject would be scanned. It has been shown that in principle the elements hydrogen, chlorine, calcium, and nitrogen [the latter using large NaI(T1) detectors] could be measured with such a facility at an average body dose level of 0.1 rad. At this dose level the coefficients of variation based on counting statistics alone would be +/- 2%, or better, for these four elements. With an improvement in the detector/spectrometer energy resolution, the elements sulfur and carbon might also be measurable. It is also shown that by modifying the pulsing sequence appropriately and using 14-MeV neutrons, total body oxygen could also be measured at the 0.1 rad dose level via its inelastic neutron scattering deexcitation gamma activity.